A Simple Model for Binding and Rupture of Bacterial Cells on Nanopillar Surfaces. Issue 10 (16th April 2019) - Watson, Gregory S.; Green, David W.; Watson, Jolanta A.; Zhou, Zupeng; Li, Xin; Cheung, Gary S. P.; Gellender, Marty
Abstract: Surfaces based on both chemical and physical mechanisms of attack may yield the next generation of bactericidal and antibacterial surfaces. A simple model is presented based on surface energies explaining the physical action of attack on bacteria (deformation/rupture) by nanopillar surfaces. The analysis is subject to three important constraints which impact on the optimal nanopillar radius, spacing, and length: 1) Nanopillar radius >> the Minimum nanopillar radius which allows for cell wall conformation (so that the surface energy releases when the outer cell layer binds to the nanopillar > work required to bend the layer around the nanopillar). 2) The inter‐nanopillar spacing must be << the size of the bacterial cell (so that the cell becomes bound to several nanopillars). 3) The length of the nanopillars must be greater than the distance that the bacteria cell wall would be pulled along the nanopillar shaft. Abstract : In the battle against pathogenic bacteria, (bio)chemistry is losing. A physical action of attack via deformation and rupture by nanopillar‐adorned surfaces is a potential alternative. A simple model is presented explaining bacterial death via this physical contact with nanopillars, based on surface energies.